Comparing the different viewpoints on overseas transplantation demands between genders and roles. Issue 1 (8th January 2021) - Chen, Hong-Mei; Shih, Fu-Jong; Hu, Rey-Heng; Shih, Fu-Jin; Sheu, Shuh-Jen
Abstract : Abstract: This study examined the different demands for overseas liver transplantation between genders and roles from the perspective of overseas liver transplant recipients and primary caregivers. An exploratory qualitative method was employed using a purposive sample of individuals who had received overseas liver transplantation. We recruited 28 recipients and 29 family members from a leading hospital in Taiwan. Face-to-face semi-structured interviews were conducted with each participant, and data were analyzed using qualitative content analysis. Three demands were identified across gender and roles: sufficient information related to overseas liver transplantation, domestic availability of the liver source, and supportive policy for receiving continuous treatment and health insurance cover. Different patterns and meanings related to gender and roles were discussed. Male recipients were less enthusiastic about receiving the overseas liver transplantation. Rather, they complained about losing the economic and decision-making power due to body deterioration after overseas liver transplantation. Their primary need was to increase their dignity and significant position in the family. Female recipients were apprehensive for overseas liver transplantation and required more psychological support and positive experiences from other transplant recipients. Most male primary caregivers required a nursing aide quickly. Most female primary caregivers would engage in the health care task but needed more medical personnel, assistance, and high emotional support from relatives. This study revealed the common and urgent demands of overseas liver transplant recipients and primary caregivers. The unique demands of recipients and primary caregivers based on their gender and roles were rooted in the potential influences of traditional cultures and modern medicine in an ethnic-Chinese society.